Kebijakan Pendidikan Jasmani Dalam Pendidikan Sekolah Dasar - Enggelita Benu; Omalia Y Abanat; Maria R Nona; Teofano R Dos Santos (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to examine the physical education curriculum policy at the elementary school level, with a focus on the implementation of the Merdeka Curriculum at SD Inpres Kobelete. Using qualitative descriptive methods, data was collected through interviews with PJOK School Principals and Teachers. The research results show that the Merdeka Curriculum provides flexibility for educators to design learning that suits students' needs. Differentiated learning strategies are applied to meet the diversity of students' learning needs, interests and learning profiles. Efforts to increase students' active participation are carried out through various methods, including practical learning, group discussions, and giving appreciation. The main challenge faced is limited learning resources. This research highlights the importance of curriculum adaptation to create an inclusive and effective learning environment in the context of physical education in elementary schools.